The Jocose prisoner and Honest Cryer. NB a Joke may be carried too far. - (:unkn) unknown (Fores, S. W., 1801)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Courts; Irish -- Caricatures and cartoons ?